#TITLE_ALTERNATIVE# - ADRIANSYAH PUTRA (NIM : 12211050), FARIZ
To calculate the Initial Gas In Place (IGIP) using P/Z material balance method, production and reservoir pressure data are needed to do the analysis, whereas reservoir pressure data usually not measured regularly from time to time. This method will give good results if used for reservoir that does not have a driving mechanism, especially strong water or this method is used in very weak water drive, so the effect of driving mechanism can be neglected. In this study, the curve of P / Z vs. Gp was modificated from material balance equation by including parameters of water influx, water production, and compressibility. The pressure used in this study is the reservoir pressure. On the other hand, well head pressure data is usually available, so it needed a method to calculate reservoir pressure using well head pressure which is the Beggs and Brill pressure loss principal and future IPR Aquifer properties are the parameter that is discussed in this study. Aquifer produces water influx that can not be ignored. With the presence water influx from the aquifer, there is a tendency to curve P / Z deviate from the conditions should be, which is a straight line. And It is difficult to obtain the actual value of IGIP. Additionally, in this study conducted an analysis of IGIP value obtained from the proposed modification P/Z method, conventionalP/Z methods and IGIP value of reservoir models. P / Z conventional method without compressibility has errors that take into account the 330.52 % and 245.06 % for the model with calculation the value of compressibility. Proposed modification P/Z method calculates the influence of water influx, compressibility and water production, the error is obtained about 1.45 % and without the compressibility is about 10.063 %. The sensitivity analysis performed on the aquifer properties to measure how much influence aquifer properties in the estimation of IGIP. The method which is used in this study is the purposed modification P / Z method. The Maximimum error obtained from the aquifer porosity parameter reaches 2.123 %. For maximum error aquifer thickness parameter reaches 2.964 %. whereas for the parameters total aquifer permeability and R-ratio can be reached 2.148 % and 1.548 %. See fairly large error is generated from P/Z conventional method, it becomes a concern that the presence of the aquifer should not be neglected. In the petroleum industry, the maximum allowed error is 25%. So the study of the properties of this aquifer could be a reference in the oil industry in determining IGIP on reservoir gas with bottom water drive driving mechanism.